Analisis persebaran hidrokarbon pada reservoir batupasir menggunakan AVO dan pemodelan probabilitas fluida pada sumur menggunakan metode AVO fluid inversion (Studi kasus lapangan “YMK” formasi Talang Akar, Cekungan Jawa Barat Utara) - Prasetyo Abdi; Hernowo Danusaputro; Mualimin Mualimin (Youngster Physics Journal, 2017)
AVO analysis methods can be used to determined the hydrocarbon zones through AVO attribute that is a function of P wave velocity, S wave velocity and density. Map attributes are the result of AVO inversion process. Based on results of AVO response can be seen that the target area is a class IIp gas sand which is characterized by polarity reversal. AFI method provides results of probability modeling in wells using fluid substitution based on Gassmann’s equation. Fluid substitution result that consisting of P wave velocity, S wave velocity and density then used as input to get the intercept and gradient of each fluid brine, oil and gas. By adding a synthetic form of attribute data simulation intercept and gradient for various possible fluid content, probabilities can be calculated using Bayes' theorem. In this study the spread of hydrocarbons can be illustrated by a map of attribute and probabilities in the wells can also be known based on synthetic data from simulation. Analysis showed that the method AFI containing oil wells are wells SNI-01 with a probability value of 0.70 and containing gas wells are wells SNI-03 with a probability value of 0.68.Keywords: AVO, Fluid inversion, hydrocarbon, reservoir, probability